Conditional Variational Autoencoder Networks for Autonomous Vehicle Path Prediction - Jagadish, D. N.; Chauhan, Arun; Mahto, Lakshman (Neural processing letters, 2022)
Mobility of autonomous vehicles is a challenging task to implement. Under the given traffic circumstances, all agent vehicles’ behavior is to be understood and their paths for a short future needs to be predicted to decide upon the maneuver of the ego vehicle. We explore variational autoencoder networks to get multimodal predictions of agents. In our work, we condition the network on past trajectories of agents and traffic scenes as well. The latent space representation of traffic scenes is achieved by using another variational autoencoder network. The proposed networks are trained for varied prediction horizon. The performance of a network is compared with other networks trained on the dataset.